External Memory Drives: Deletion and Digitality in Agrippa (A Book of The Dead). - Swanstrom, Lisa (Science Fiction Studies, 2016)
While William Gibson's cyberpunk fiction is fundamental for understanding the relationship between digitality and science fiction, I suggest that Gibson's most important "digital" work is neither cyberpunk, science fiction, nor even fiction. It is, instead, an autobiographical poem, Agrippa: (A Book of The Dead), published in 1992. Agrippa marks a pivotal point in Gibson's writing for its engagement with actual-as opposed to speculative-digital editing techniques, not merely in terms of the disk that contains the poem encoded within it, but in terms of Gibson's tendency to triangulate digitization, identity, and memory. Agrippa as a whole-that is, as a work of poetry, a printed book, and a self-effacing digital object-functions initially as a modernist monument to subjectivity at the very moment of its dismantling and, in this respect, is wholly consistent with Gibson's cyberpunk fiction, which tends to treat digital technology in analog terms. Yet in the twenty-plus years since its initial publication, Agrippa has continued to evolve, and a reading of this strange text today yields different possibilities. In what might be termed Agrippa's afterlife, a more fluid form of memory has emerged, one that is collective, participatory, collaborative, and much more in tune with the nature of digitality.